(untitled) (Revista Educação, Artes e Inclusão, 2025)
The invention of putting into dialogue Francisco de Goya and Ai Weiwei, two artists and their works absolutely distinct and distant in history, is playing with the temporal virtuality that governs acting and remaining forces even after death, in ’eternal return’. Thus, this text is proposed here as a narrative construction that seeks to circumvent historical contiguity in the intention of reopening problems, which can always be perceived under new looks and perspectives, in order to find facets still unexplored of artistic language. Art and politics establish their productions that negotiate, administer and potentiate the forces that operate on the bodies in diverse flows of deformation, mutation and rearrangements in the confluence of heterogeneous times.